(3GdCehGds - (3CHh LYaQ CMeO Hf fUQ GdOGhOj GdeGdcj, GdOGhOj,J (B307 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbgGQ aef Pdc GdESdGe hgh GdEbQGQ HGddg hedGFcJg hcJHg s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3hdh GZadhG Pdc hXfhG Cf GdaVd ai ZjQg dHjf Gddg Pdc ZjQ Cf CaGJ GdZfi CcKQ hGdfGLhf ef Cgdg Cbdg EP dG jcGO Cf jSde ef BaGJg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B264s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis